2021
DOI: 10.1016/j.jbc.2021.100306
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infects cells after viral entry via clathrin-mediated endocytosis

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of COVID-19, so understanding its biology and infection mechanisms is critical to facing this major medical challenge. SARS-CoV-2 is known to use its spike glycoprotein to interact with the cell surface as a first step in the infection process. As for other coronaviruses, it is likely that SARS-CoV-2 next undergoes endocytosis, but whether or not this is required for infectivity and the precise endocytic mechanism used are unkn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
322
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(368 citation statements)
references
References 53 publications
11
322
2
1
Order By: Relevance
“…For instance, Ou et al identified the SAS-CoV-2 receptor, entry pathway and potential drug targets by using SARS-CoV-2 S protein pseudovirus system [ 52 ]. Bayati et al developed SARS-CoV-2 S protein pseudovirus to study the virus entry, which confirmed that SARS-CoV-2 used clathrin-mediated endocytosis to get into cells [ 53 ]. Besides, Wibmer et al employed pseudovirus model to evaluate the responses of therapeutically relevant antibodies to SARS-CoV-2 [ 54 ].…”
Section: Resultsmentioning
confidence: 98%
“…For instance, Ou et al identified the SAS-CoV-2 receptor, entry pathway and potential drug targets by using SARS-CoV-2 S protein pseudovirus system [ 52 ]. Bayati et al developed SARS-CoV-2 S protein pseudovirus to study the virus entry, which confirmed that SARS-CoV-2 used clathrin-mediated endocytosis to get into cells [ 53 ]. Besides, Wibmer et al employed pseudovirus model to evaluate the responses of therapeutically relevant antibodies to SARS-CoV-2 [ 54 ].…”
Section: Resultsmentioning
confidence: 98%
“…Expression level of these proteases depends on cell type and hence their relative importance to support successful infection would hinge in part on their relative expression. Cathepsin is primarily found in late endosomes or lysosomes and requires low pH for optimal enzymatic activity; for these reasons it has been proposed that SARS-CoV-2 entry occurs from the endolysosomal compartment (32, 33). In contrast, TMPRSS2 is thought to be at the cell surface (34) and its optimal proteolytic activity is pH independent (35); hence it has been inferred that TMPRSS2 cleavage of spike S protein occurs on virions at the plasma membrane from which viral entry is then assumed to occur (1).…”
Section: Resultsmentioning
confidence: 99%
“…Here by using different chemical inhibitors and CRISPR/Cas9 targeting the major protein in clathrin coat formation, we demonstrated that SARS-CoV-2 entry also was dependent on clathrin. While we are preparing this manuscript, Bayati et al reported that the Spike protein of SARS-CoV-2 endocytosis is dependent on clathrin and S pseudovirus can be blocked by CHC siRNA treatment(42). Consistently, we also showed that SARS-CoV-2 pseudovirus enters cell via CME, in addition, we also showed that this process is independent of caveolae-mediated endocytosis, another common endocytosis pathway.…”
Section: Discussionmentioning
confidence: 99%